The mediating effect of school climate on transformational leadership and school effectiveness - Maniam, Indra Devi; Lope Pihie, Zaidatol Akmaliah (ARC Publications, 2017)
The purpose of this paper is to develop a conceptual model in exploring the mediating effect of school climate on transformational leadership and school effectiveness in Malaysian primary schools. As such, this conceptual paper was developed based on three theories: School Effectiveneess Theory (Lezzote and Kynder, 2011), Transformational Leadership Theory (Leithwood and Jantzi, 2000) and School Climate Theory (Wayne K. Hoy, 2003). Upon extensive review on the past studies, four dimension of Transformational Leadership, four dimensions of School Climate and seven dimensions of School Effectiveness were identified to contrast this model.